Design visual e credibilidade percecionada na web : análise empírica de websites no sector da saúde - Sequeira, Mafalda Sofia de Sousa, 1989- (2015)
This study investigates the relationship between the visual design of websites in the health sector, notably hospitals' and clinics' websites, and the credibility awarded to them by users. The credibility assessment of online health information is particularly important due to its common use as a means of self-diagnosis, where the actions resulting from dubious and erroneous information may have dire consequences, especially if compared to other areas. In the online context, and in particular to websites, four categories of awarded credibility are identified: presumed (based on personal assumptions); reputed (based on the prestige and reputation of the sources); earned (based on past experience) and surface (based on the visual characteristics of the pages). This research, with an empirical basis, focuses on superficial credibility and tests the theoretical assumption that web pages with good visual design are perceived as more credible than pages with poor visual design. It also seeks to identify the visual elements that exert more influence on the perception of credibility and verifies the existence of judgement variations depending on users' demographic profile and computer skills. The findings clearly show the existence of a strong correlation between the quality of the visual design of a web page and the perception of its credibility, thus verifying that websites with good visual appearance are effectively perceived as more credible than websites with poor visual appearance. Imagery, organisation and visual structure, colours and patterns are the main factors for the attribution of credibility. This study is the first to try and isolate the visual component of websites, minimising the impact of other factors such as textual content, logos and visual references of sources, in order to assess specifically the importance and influence of visual appearance in the perception of credibility. It is also the first, in the Portuguese context, to examine the relationship between visual design and perceived credibility of websites in the health sector, and a precursor in the identification of the visual elements that contribute to the perception of superficial credibility